Replacement name for a homonym in Typhlodromus Scheuten (Acari: Phytoseiidae) - Lofego, Antonio C.; Feres, Reinaldo J.f. (Zootaxa, 2007)
Lofego & Feres (2006) described a new species of phytoseiid mite of the genus Typhlodromus, named Typhlodromus moraesi Lofego & Feres. A different species of Typhlodromus had already been named T. moraesi Kreiter & Ueckermann (2002), but was not included in the catalogue of Moraes et al. (2004). T. moraesi Lofego & Feres is a junior homonym of T. moraesi of Kreiter & Ueckermann, and is an invalid name according to Article 57 of the International Code of Zoological Nomenclature (ICZN, 1999). Therefore, Typhlodromus demoraesi nom. nov. is here proposed as a replacement name. As for the original name, the new specific name, T. demoraesi, is in honor Gilberto J. de Moraes, the eminent Brazilian acarologist.